Exploring Indigenous Knowledge as Curriculum Knowledge for the Life Sciences Curriculum and Assessment Policy Statements: What Rural Communities Can Offer in South Africa - Lefora, Neo (University of the Witwatersrand, Johannesburg, 2024)
The study focused on collecting, documenting, and describing Indigenous Knowledge which could be relevant to teaching and learning grade 12 Life Sciences CAPS in a rural South African community. The aim of the study was to create a database of Life Science-related Indigenous Knowledge and propose how it may be integrated with the current grade 12 Life Sciences curriculum. The methodology involved a qualitative indigenous research paradigm centred on Ubuntu approach. Data was collected from 10 community elders through interviews while 6 participated further in focus group discussion. Through thematic analysis, three themes emerged from the data: the knowledge of traditional plants and herbs, knowledge regarding sustainability processes for the traditional plants and herbs, and the knowledge of traditional and cultural practices. The findings show that the Indigenous Knowledge which is used for health and cultural-spiritual purposes is relevant to the grade 12 Life Sciences CAPS. This includes the community’s understanding and use of Artemesia Afra and the African Potato for flu symptoms and diabetes, respectively, which can be explained scientifically. However, some of this knowledge exceeds the scope of Western scientific understanding. The making of Umqombothi as a traditional type of prayer and the burning of Helichrysum Odoratissimum as a way of inviting the presence of the ancestors demonstrates the relational ontology of the community members. The study argues for an intersecting approach to integration in which Indigenous Knowledge is integrated with the grade 12 Life Sciences content at the point of factual and procedural knowledge. This implies integrating Indigenous Knowledge along with associated values and beliefs without compromising the science in the curriculum. In this way, the curriculum is decolonised by adopting a Pluriversal approach to knowledge.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Indigenous Knowledge; Decolonisation; Life Sciences CAPS; Pluriversality; SDG-4: Quality education